Аналіз методів контейнеризації програмного забезпечення - Прес, Р. Д. (ХНУРЕ, 2024)
Effective software environment management and deployment are essential for success in today's IT sector. The goal of this study is to learn more about containerization technologies. It compares several methods of software environment deployment and examines the benefits of containerization. The study's conclusions will help project managers and IT professionals deploy software more effectively and maintain system scalability and stability by using containerization.
Keywords: контейнеризація програмного забезпечення; Docker; Podman; Kubernetes